ANALISIS TINGKAT PENGETAHUAN DAN PERILAKU DALAM MENGKONSUMSI VITAMIN D3 DAN E PADA KONSUMEN DI APOTEK X BADUNG - Ika Indah Indraswari, Putu; Ayu Apriliani; A.A Bagus Suryantara (Journal Pharmactive, 2025)
Vitamins are organic substances that cannot be synthesized by the body and are classified into fat-soluble and water-soluble types. Vitamins D3 (cholecalciferol) and E (tocopherol) are among the most frequently consumed by the public to meet daily nutritional needs and support immune function. This study aimed to analyze the level of knowledge and behavior of respondents regarding vitamin consumption and to examine the influence of age and last education level on these two variables. This research employed a prospective method with a quantitative approach. A total of 86 respondents were selected using purposive sampling. Data were collected using structured questionnaires and analyzed using SPSS software with the Chi-Square test. The results showed that there was no significant relationship between knowledge level and either age or education level (p > 0.05). However, there was a significant relationship between behavior and age (p < 0.05), while no relationship was found between behavior and education level (p > 0.05). These findings indicate that age plays an important role in shaping vitamin consumption behavior, although it does not directly influence knowledge. Meanwhile, the last level of education does not significantly affect either knowledge or behavior. An educational approach that takes age into account as a dominant factor is needed to improve behavior regarding vitamin consumption.